Rhizofiltration of water contaminated with heavy metal using impatiens balsamina plant / Syazuani Mohd Shariff … [et al.] - Mohd Shariff, Syazuani; Wan A. Kadir, Wan Ramlee; Nawahwi, Mohd Zaini; Ahmad Wakid, Sarini; Jaafar, Zuraida; Rahim, Muhammad Izzat (Research Management Institute (RMI), 2016)
The Earth is poised at the brink of a severe environmental crisis. Current environmental problems make its living communities vulnerable to disasters and tragedies in future ongoing. The changes in the environment has urged public to increase their awareness towards the problems that surround it. All across the world, pollution issue has become one of the critical environmental problems especially in developed and developing countries. Pollution of air, water and soil required millions of years to recoup. Human activities responsible for the pollution directly, meanwhile fertilization activities in agricultural farming caused the leaching process of abundance of concentrated essential nutrients in the soil. Excessive production amount of waste from industrial activities without proper disposal ethic and mechanism also contributed to the mobilization of hazardous contaminants thoroughly from soil to the underground water supply. Due to the increasing accumulation of heavy metals in the underground environment, it has urged scientists to come out with new technologies to restraint and/or reduce the toxicity level of contaminant substances in the polluted aquatic environment. This is a very challenging job with respect to cost and technical complexity (Barcelo and Poschenrieder, 2003). In fact, the introduced conventional method in cleaning the polluted aquatic sites such as in situ vitrification, microfiltration and sedimentation techniques, solidification, and stabilization of electro-kinetic systems suffer from limitations, such as costly, intensive labor, irreversible changes in physico-chemical properties in aqueous and disturbance of native micro-flora, hence potentially create secondary pollution problems (Sheoran et al., 2011). Since the conventional method mostly proved to be partially effective in decontaminating hazardous heavy metals in the environment, researchers have came out with a variety of biological sources that have been employed widely in developed and developing nations for the cleanup approaches. The basic idea of exploiting plants ability to decontaminate polluted sites has gained considerable momentum in early 1900's, when scientist from Soviet Union develop the concept of geobotany, known as the study of plants ability to grow dependence on environment (Rawat et al., 2012).